(untitled) (World Bulletin of Management and Law, 2022)
The purpose of this study was to investigate the effect of accounting information systems characteristics on improving the financial performance of public contractors through the mediating role of audit quality. Descriptivecorrelation method was used to conduct this research. The statistical population of the present study included an unlimited number of accountants, auditors and financial managers of public contracting companies operating in the city of Baghdad-Diwaniyah. Based on the Cochran’s formula, a total of 385 required sample sizes were determined. A questionnaire with 48 questions was used to examine the research variables. The reliability of the questionnaires was confirmed by Cronbach’s alpha coefficient, the content validity of the questionnaires was confirmed by a group of university professors and their construct validity was confirmed by confirmatory factor analysis. Parametric statistical methods such as Kolmogorov-Smirnov test have been used to ensure the normality of the data and the model of structural equations and path analysis using LISREL software to test the hypotheses. The most important research findings showed that; The relationship between accounting information systems through the mediating role of audit quality has a positive and significant effect on improving financial performance. The accuracy of accounting information systems has a positive and significant effect on improving financial performance through the mediating role of audit quality. The verifiability of accounting information systems through the mediating role of audit quality has a positive and significant effect on financial improvement. The timeliness of accounting information systems through the mediating role of audit quality has a positive and significant effect on improving financial performance